Economic Fluctuations in a Small Open Economy - Real versus Nominal Shocks - Hilde C. Bjørnland (Statistics Norway, Research Department, 1998)
This paper analyses the role of real and nominal shocks in explaining business cycles in a small open economy like that of Norway. In particular, we study the sources behind real exchange rate fluctuations since the collapse of the Bretton Woods agreement. Imposing long run restrictions implied by economic theory on a structural vector autoregression (VAR) model containing GDP, unemployment (or price), real wage and the real exchange rate, four structural shocks are identified; Velocity (or monetary), fiscal, productivity and labour supply shocks. The model is also augmented to allow for oil price shocks.The identified shocks and their impulse responses are consistent with an open economy (Keynesian) model of economic fluctuations, and highlights the exchange rate as a transmission mechanism in a small open and energy based economy. Especially, I have found a plausible sequence of shocks (productivity shocks in the 1970s, velocity shocks in the mid-1980s, productivity and labour supply shocks in the late 1980s, and velocity and fiscal shocks in the early 1990s), which help to explain the evolution of GDP, unemployment, price, real wage and the real exchange rate. The results are robust to alternative specifications of the model and are stable over the sample.
Keywords: C32; E32; E63; F41; 330; Real and nominal shocks; exchange rate fluctuations; purchasing power parity; dynamic restrictions; structural VAR